2005
DOI: 10.1038/oby.2005.240
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Whole and Refined Grain Breakfast Cereals and Weight Gain in Men

Abstract: BMI and weight gain were inversely associated with intake of breakfast cereals, independently of other risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
147
1
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(164 citation statements)
references
References 24 publications
10
147
1
6
Order By: Relevance
“…In large prospective studies, a consistent inverse association between whole-grain consumption and self-reported weight gain was reported in women (Liu et al, 2003) and men (Koh-Banerjee et al, 2004). In a prospective study among male physicians, consumption of breakfast cereals was inversely associated with selfreported weight gain (Bazzano et al, 2005). These results correspond to our cross-sectional findings in both men and women.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In large prospective studies, a consistent inverse association between whole-grain consumption and self-reported weight gain was reported in women (Liu et al, 2003) and men (Koh-Banerjee et al, 2004). In a prospective study among male physicians, consumption of breakfast cereals was inversely associated with selfreported weight gain (Bazzano et al, 2005). These results correspond to our cross-sectional findings in both men and women.…”
Section: Discussionsupporting
confidence: 90%
“…The association between the consumption of whole grains and several diseases has been studied (Jacobs et al, 1998;Jacobs and Gallaher, 2004;McKeown, 2004;Merchant et al, 2006), but thus far only few studies have reported on the association between whole-grain intake and BMI (McKeown et al, 2002;Koh-Banerjee and Rimm, 2003;Steffen et al, 2003) and (changes in) whole-grain intake and weight gain (Liu et al, 2003;Steffen et al, 2003;Koh-Banerjee et al, 2004;Bazzano et al, 2005) and dietary fibre intake and body weight (Slavin, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the Women's Health Initiative observing 48 835 women over a 7-year period, low-fat diet with increased fruits, vegetable and grain consumption was associated with weight loss or prevention of weight gain (Howard et al, 2006), whereas a traditional diet in Brazil consisting Table 2 Factors associated with the development of overweight (Sichieri, 2002). Similarly, consumption of whole or refined grain breakfast cereal was inversely related to weight gain adjusting for multiple confounding factors, in 17 881 US male physicians followed up for 4-13 years (Bazzano et al, 2005). Snacks and fast foods consumption appear to be associated with overweight/ obesity in studies in Iran (Kelishadi et al, 2003), India (Ghosh et al, 2003), USA (Nicklas et al, 2003), US Latino population (Hubert et al, 2005), Chinese (Fu and Hao, 2002;Waller et al, 2003) and US children (Francis et al, 2003;Sothern, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies among Chinese populations examining the role of dietary intake, taking into account other confounding factors such as age, physical activity, gender and educational attainment. Other than the effect of total energy and macronutrient intake (Halkjaer et al, 2006) on development of overweight and obesity, recent studies have highlighted the role of dietary patterns in terms of meal frequency and timing, and types of food consumed (Kirk, 2000;Sichieri, 2002;Francis et al, 2003;Ghosh et al, 2003;Kelishadi et al, 2003;Nicklas et al, 2003;Waller et al, 2003;Bazzano et al, 2005;Hubert et al, 2005;Howard et al, 2006). For example, patterns predisposing to overweight and obesity include a 'Westernized' pattern compared with a 'traditional' pattern for the population studied (Sichieri, 2002;Ghosh et al, 2003;Hubert et al, 2005) and snacks consumption (Fu and Hao, 2002;Francis et al, 2003;Sothern, 2004;Hubert et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, research findings from a prospective study (30) showed that BMI and weight gain were inversely associated with intake of breakfast cereals independently of other risk factors. The study sample consisted of 17 881 US male physicians aged 40 -84 years.…”
Section: Adultsmentioning
confidence: 99%